A study of Traditional Games “Engklek” in Mathematics for Elementary School - Asrial, Asrial; Syahrial, Syahrial; Maison, Maison; Kurniawan, Dwi Agus; Perdana, Rahmat (Universitas Negeri Malang, 2020)
This study aims to determine whether elementary school teachers know the traditional game